Seed Inoculation with Halotolerant Strains Enhance Brassicaceae Seedling Establishment Under Saline Conditions - Carlos González-Cobo; Glòria Escolà; Roser Tolrà; Mercè Llugany; Charlotte Poschenrieder; Eliana Bianucci; Silvia Busoms (Agriculture)
Soil salinity inhibits germination and seedling establishment, causing patchy crop stands, uneven growth, and poor yields. This study aims to evaluate the early-stage salinity tolerance of Brassicaceae seeds inoculated with plant growth-promoting bacterial (PGPB) strains (E1 and T7) isolated from saline soils. Non-inoculated and inoculated seeds of Lobularia maritima, Sinapis alba, and Brassica napus were cultivated under control and salinity conditions, first in agar plates to assess a germination inhibitory concentration of salt for each species and later in soil irrigated with water containing 0 or 75 mM NaCl. Our results indicate that T7 was the only strain able to increase the germination of L. maritima under saline conditions. However, an increase in shoot biomass, root length, and number of branches was observed in L. maritima and S. alba plants inoculated with T7 and in B. napus with E1. Concomitantly, those seedlings exhibited less oxidative damage and greater capacity to balance plant reactive oxygen species production. This study suggests that inoculation of seeds with halotolerant PGPB strains is a suitable strategy for improving the negative effects of salinity in the early stages. Nonetheless, the observed specific plant–host interaction highlights the need for establishing tailored PGPB–crop associations for specific unfavourable environmental conditions.